PENERAPAN NARASI SUGESTIF DALAM PENULISAN NASKAH PADA VIDEO FEATURE QUIET QUITTING - Raemada, Helen Syahnia; Zubair, Feliza; Yuliani Dewi Risanti (AT-TAWASUL, 2025)
The feature video Quiet Quitting: The Balance Within explores the quiet quitting phenomenon, where employees work within their responsibilities without extra effort for work-life balance. This study analyzes the use of suggestive narration in its script. A qualitative descriptive analysis with a script study approach examines its application within the Three-Act Structure (introduction, development, resolution). The findings show that suggestive narration effectively enhances audience engagement through meaningful diction, figures of speech (metaphor, personification, hyperbole), and visuals that reinforce the narrative. The introduction presents quiet quitting through personal experiences, the development illustrates its psychological impact on workers, and the resolution offers expert insights as solutions. This study confirms that suggestive narration strengthens audience comprehension of social issues and deepens emotional connection to the story